POLITICAL WILL PEMERINTAHAN DAERAH KABUPATEN SIAK MEWUJUDKAN E- GOVERNMENT DI BIDANG INVESTASI TAHUN 2021 - Afrianti Rizki; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Licensing Service Information System, abbreviated as SMILE, is one of the breakthroughs in the smart city program by the Siak Regency Government which can be categorized according to the Government to Business concept which makes interaction between the two parties, namely the government and the business community, to help facilitate the implementation of public services in the field of licensing that can accessed by the community for free by the community in the device. The problem of this research is what is the political will of the Siak Regency government to realize E-Government in the field of investment services. This study uses Derick W. Brinkerhoff's grand theory, namely the political will component and Indrajit's supporting theory, which is related to the determinants of readiness for implementing E-Government in the regions. The research method used is a qualitative method. This type of research is descriptive. The research location is in Siak Regency, to be precise at the One-Stop Investment and Services Agency and supporting parties on the SMILE Website. Types and sources of research data are divided into primary data using a purposive technique of collecting informants and secondary data in the form of supporting data related to SMILE. The data analysis technique used is data collection techniques from Miles and Hubermas. The results of this study are that the Political Will of Regional Government to realize E-Government in the field of Investment in 2021 is running optimally with the fulfillment of 4 indicators of government initiatives, Choice of Priority Policies/Programs, Public Commitment and Resource Allocation and Learning and Adaptation. However, there were 2 components of Political Will found to be slightly lacking, namely, the mobilization of the parties and business continuity. The obstacles that underlie the process